Case Report: Paternal Uniparental Isodisomy and Heterodisomy of Chromosome 16 With a Normal Phenotype - Zhang, Xu; Liu, Li; Liu, Yang; Pan, Xin (Frontiers in Pediatrics, 2021)
Uniparental Disomy (UPD) is a specific type of chromosomal variant that has been detected in both prenatal diagnosis and neonates with advances in molecular genetic testing technologies (mainly CMA technologies containing SNP probes). In this case, we performed non-invasive prenatal genetic testing (NIPT) to screen fetuses for aneuploidy and detected the presence of aneuploidy chimerism and uniparental disomy by chromosome microarray analysis (CMA), including SNP analysis, and whole exome sequencing (WES) to detect pathogenic variants within the genome. The NIPT results suggested an increased number of fetal chromosome 16, and the CMA results indicated that it was the first case of a holistic paternal UPD16 with isodisomy combined with heterodisomy, and no abnormal phenotype was seen in the newborn at postnatal follow-up. A retrospective analysis of this case of paternally derived UPD16 was used to explore the uniparental diploid origin of chromosome 16 and to provide some reference for genetic counseling and prenatal diagnosis.